2000
DOI: 10.1128/mcb.20.24.9376-9390.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Inositol Polyphosphate 5-Phosphatases Inp52p and Inp53p Translocate to Actin Patches following Hyperosmotic Stress: Mechanism for Regulating Phosphatidylinositol 4,5-Bisphosphate at Plasma Membrane Invaginations

Abstract: The Saccharomyces cerevisiae inositol polyphosphate 5-phosphatases (Inp51p, Inp52p, and Inp53p) each contain an N-terminal Sac1 domain, followed by a 5-phosphatase domain and a C-terminal proline-rich domain. Disruption of any two of these 5-phosphatases results in abnormal vacuolar and plasma membrane morphology. We have cloned and characterized the Sac1-containing 5-phosphatases Inp52p and Inp53p. Purified recombinant Inp52p lacking the Sac1 domain hydrolyzed phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 47 publications
5
49
0
Order By: Relevance
“…However, this has yet to be shown. Recently our laboratory has demonstrated that Inp52p and Inp53p are localized diffusely throughout the cell excluding the nucleus and translocate to cortical actin patches following hyperosmotic stress (21). The intracellular localization of Inp51p has not been delineated, as the enzyme is extensively proteolyzed when expressed as a recombinant protein (21,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this has yet to be shown. Recently our laboratory has demonstrated that Inp52p and Inp53p are localized diffusely throughout the cell excluding the nucleus and translocate to cortical actin patches following hyperosmotic stress (21). The intracellular localization of Inp51p has not been delineated, as the enzyme is extensively proteolyzed when expressed as a recombinant protein (21,55).…”
Section: Discussionmentioning
confidence: 99%
“…Transformants were selected by their ability to grow on complete minimal media lacking leucine, and were subsequently screened for homologous integration of the LEU2 marker by PCR. Null mutations of the SacI domain-containing 5-phosphatases has been described previously (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, PKC will make a positive-feedback circuit by enhancing the PIP 2 hydrolysis, and play a role of signal amplifier. PKC activation can also reduce the membrane PIP 2 content by regulation of the phosphatidylinositol transfer protein (35), and regulation of activity and location of lipid phosphatases and/or lipid kinases (21,22). The molecular identity of lipid kinases and phosphatases regulating the PIP 2 metabolism remain controversial.…”
Section: Fig 6 Pkc Sensitivity Of Girk Channels Depends On Channel-mentioning
confidence: 99%
“…INS51 has genetic interactions with PAN1, a protein required for endocytosis and regulation of actin (380). Inp52p and Inp53p have both 5-phosphatase activity as well as Sac domain phosphatase activity and are involved in regulating actin patches at the plasma membrane (PM) (260,338). Disruption of INP53, but not INP51 or INP52, causes sorting defects at the TGN and increases the rate of transport of reporter proteins to the vacuole (19,125).…”
Section: Sac Family Phosphatasesmentioning
confidence: 99%